Mechanic Characterization of Natural Rubber Mixtures and Cellulose Waste from the Automotive Sector with a Focus on the Footwear Industry - Arias-Jaramillo, Maria Isabel; Dos Santos, Jose Renivaldo [UNESP]; Paim, Leonardo Lataro [UNESP]; Barrera-Torres, Giovanni (Univ Distrital Francisco Jose De Caldas, Centro Invest & Desarrollo Cient, 2023)
Context: This publication shows a potential use for waste from the automotive industry, namely waste originating in the manufacturing process of gaskets and seals for motorcycles, which currently do not have a final use. In addition, due to their high-performance rubber surface layer, they imply an extensive degradation process, which constitutes a harmful factor for the environment and contributes to global warming. Method: First, the crushing of the residues was carried out, then their sieving and selection via granulometry, and finally a mixture with the natural rubber through chewing in open cylinders in order to obtain the master, which was vulcanized in a shoe sole mold. The final product was mechanically characterized via the techniques, tension-elongation, wear, hardness, bending, and tearing. Results: The obtained mixture opens a window to the design of products using residues from seals and gaskets for motors. It will be possible to design other proposals for functionalized rubbers, oriented towards the development of ecological footwear applications. Conclusions: The mixture of cellulose waste from the motor seal sector and natural rubber shows promise for the reduction of the negative impact caused by these wastes and proposes a circular economy -in this case, with the development of raw material in the footwear sector.
Keywords: natural rubber; residual cellulose; industrial waste; circular economy